2006
DOI: 10.1038/nbt1258
|View full text |Cite
|
Sign up to set email alerts
|

BMP-4 is required for hepatic specification of mouse embryonic stem cell–derived definitive endoderm

Abstract: When differentiated in the presence of activin A in serum-free conditions, mouse embryonic stem cells efficiently generate an endoderm progenitor population defined by the coexpression of either Brachyury, Foxa2 and c-Kit, or c-Kit and Cxcr4. Specification of these progenitors with bone morphogenetic protein-4 in combination with basic fibroblast growth factor and activin A results in the development of hepatic populations highly enriched (45-70%) for cells that express the alpha-fetoprotein and albumin protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
391
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(417 citation statements)
references
References 44 publications
21
391
1
2
Order By: Relevance
“…Gouon-Evans et al [58] generated an endoderm progenitor population by culturing ES cells in the presence of activin in serum-free conditions, and specified these progenitors with BMP-4, activin, and fibroblast growth factor (FGF) in the development of hepatic populations highly enriched (45-70%) for cells expressing albumins. During embryogenesis, expression of Pdx1 (pancreatic and duodenal homeobox gene 1) marks the dorsal and ventral pancreatic buds, which generate all pancreatic lineages, i.e.…”
Section: Endoderm Derivativesmentioning
confidence: 99%
“…Gouon-Evans et al [58] generated an endoderm progenitor population by culturing ES cells in the presence of activin in serum-free conditions, and specified these progenitors with BMP-4, activin, and fibroblast growth factor (FGF) in the development of hepatic populations highly enriched (45-70%) for cells expressing albumins. During embryogenesis, expression of Pdx1 (pancreatic and duodenal homeobox gene 1) marks the dorsal and ventral pancreatic buds, which generate all pancreatic lineages, i.e.…”
Section: Endoderm Derivativesmentioning
confidence: 99%
“…2 Moreover, BMP4 promotes the differentiation towards mesendodermal lineages and also regulates, either positively or negatively, the further commitment of mesendodermal precursors into their different fates. [5][6][7][8] Gene expression in ESCs is regulated by a complex network of transcription factors. 9,10 In addition, numerous results indicate that miRNAs are crucial regulators of the gene expression programs that drive ESC differentiation.…”
mentioning
confidence: 99%
“…In mouse ES cell-based differentiation systems, Brachyury is widely used as a mesoendoderm marker, and Brachyury-positive cells were able to differentiate into mesodermal and definitive endodermal lineages, such as cardiomyocytes and hepatocytes (8)(9)(10). In a previous study, we found that depletion of a core promoter factor, the TATA binding protein-associated factor 3, in ES cells leads to significant up-regulation of Brachyury and mesoderm lineages during ES cell differentiation (11).…”
mentioning
confidence: 99%